Motivational factors and post procedure impact of facial dermal fillers: a qualitative descriptive study - Hirschfeld, Eugene Rouf (Department of Medicine, 2022)
Background: Over the past decade there has been a worldwide increase in the number of minimally invasive cosmetic procedures, such as dermal fillers. As there are few studies in this field, with most focussing on cosmetic surgery, we conducted research into perceptions around use of dermal fillers, which could contribute to standards of care in administering minimally invasive aesthetic procedures. Objectives: 1. To determine the motivational factors and perceived benefits in people who have had dermal fillers. 2. To assess the need for pre- and post-procedure counselling Methods: We conducted in depth semi-structured patient interviews in people who had had dermal fillers. All 6 participants were adult women. A qualitative comparative approach was used to analyse interview scripts, generating categories and subcategories. Data was further analysed using the theory of planned behaviour. Results: Motivational factors were classified as follows: pressure from immediate social circle, occupational exposure, societal pressure, perceived benefits, and influence of media. Participants supported counselling, to establish motivational factors, screen for psychiatric disorders, gain informed consent and obtain post-procedure feedback. Limitations: Sampling was from a single dermatology practice. Participants were mostly middle-aged, White women from a high-income group. As volunteers chose to participate there may have been selection bias. Our findings may therefore have limited generalisability. Conclusions: Motivations for dermal fillers were influenced by personal and societal beliefs. The findings emphasize the importance of pre- and post-procedure counselling in cosmetic dermatology. Further qualitative research across a more diverse group might yield additional insights.